Siting of PV power plants on inclined terrains. Issue 9 (20th October 2016) - Charabi, Yassine; Rhouma, Mohamed Ben Hadj; Gastli, Adel
Abstract : Most of the studies conducted on solar energy assessment and solar system siting focus on flat terrains that are usually difficult and expensive to acquire in urban areas. This paper investigates the possibility of using inclined terrains for siting photovoltaic (PV) power plants surrounding urban area. Both analytical analysis and simulations are carried out in order to analyse and validate the effectiveness and benefits of the use of inclined land for PV siting. Geographical information system and numerical weather prediction were used to implement the suggested original approach and to select suitable inclined terrains for the PV system installation and to calculate the total generation potential for energy production. Muscat, the capital of Oman, was selected as a reference for the implementation of this approach.